Phytosome: a novel dosage form for herbal drug delivery - Choudhury, Ananta; Verma, Swati; Roy, Amit (Journal of Applied Pharmaceutical Research, 2014)
Phytosome is a complex of a natural active ingredient and phospholipids. The term âPhytoâ means plant while âsomeâ means cell like structure. It is claimed that phytosome increases absorption of "conventional herbal extracts" or isolated active principles both orally as well as topically. In this era phytosome gain popularity as a potential drug delivery device due to excessive demand and utility of herbs or herb based medicines. This advance technology offers amenities like improved absorption, enhanced delivery & increased bioavailability of herbal extracts. These drug-phospholipid complexes can be fabricated in the form of solution, suspension, emulsion, syrup, lotion, gel, cream, aqueous micro dispersions. Standardized plant extracts, mainly polar phytoconstituents like flavonoids, terpenoids, tannins, xanthones shall be introduced in form of phytosome.